KETERSEDIAAN DAN SERAPAN HARA P TANAMAN JAGUNG MANIS PADA OXIC DYSTRUDEPTS PALOLO AKIBAT PEMBERIAN EKSTRAK KOMPOS LIMBAH BUAH KAKAO - Saiful Darman (Universitas Tadulako, 2008)
The aim of the research was to determine the phosphorous availability and uptake by sweet corn plant in Palolo Oxic Dystrudepts, Central Sulawesi added with extract of cacao fruit waste compost. The experiment used a Completely Randomized Block Design with the extract levels of the cacao fruit waste compost as treatments. The applied levels of the extract were as follows: Control, 500 L ha-1, 1000 L ha-1, 1500 L ha-1, 2000 L ha-1, 2500 L ha-1, 3000 L ha-1, 3500 L ha-1, 4000 L ha-1, and 4500 L ha-1. The research results showed that the addition of the compost extract could increase soil pH, total P, available P, P uptake and plant dry weight. The soil pH, total P, available P increased with the compost extract levels and reached their maximum at the 4500 L ha-1 treatment. Whereas the largest P uptake and plant dry weight was found at the 4000 L ha-1 treatment.